Enhancing Generation Z's Awareness and Purchase Interest for Indonesian-Made Products Through Tokopedia's "Beli Lokal" Campaign - Ayralfath Adryanadi; Astuti, Prida Ariani Ambar (CoverAge: Journal of Strategic Communication, 2025)
Marketplaces in Indonesia have significant potential, but this potential is not fully harnessed by MSMEs (micro, small, and medium enterprises). Generation Z, the dominant demographic in online marketplaces, tends to favor foreign products over local ones. In response, Tokopedia, the second-largest marketplace in Indonesia, launched the "Beli Lokal" campaign to support local products in the online market. This study aims to evaluate the impact of Tokopedia's "Beli Lokal" social marketing campaign on Generation Z's awareness and interest in locally made products. The research employs a positivist paradigm with a quantitative approach, utilizing surveys and collecting data through online questionnaires targeted at Gen Z respondents who use Tokopedia. Data analysis includes validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), along with simple and multiple linear regression analyses, and t-tests. The results indicate that Tokopedia's "Beli Lokal" campaign has a significant positive effect on Generation Z's awareness of local products. Furthermore, the campaign also directly and significantly influences Gen Z's interest in these local offerings. Consequently, the "Beli Lokal" campaign is effective in enhancing Generation Z's interest in local products, both by increasing their understanding of these products and by directly engaging in their interest. These findings provide valuable insights for academic purposes and practical implications for Tokopedia's marketing strategies.